Secondary‐prevention behaviour‐change strategy for high‐risk patients: Benefits for all classes of body mass index. Issue 5 (9th January 2020) - Langston, Keanne; Ross, Lynda J.; Byrnes, Angela; Hay, Robin
Abstract: Aim: Research is needed to support the long‐term benefits of lifestyle interventions for management of high‐risk patients with different BMI classifications. This prospective multicentre study assessed two‐year outcomes of hospital‐referred patients (BMI 25‐61 kg/m 2 ) attending a dietitian‐led multidisciplinary Healthy Eating and Lifestyle Behaviour‐Change Program in group or individual formats in hospital outpatient settings. Methods: Bodyweight, quality of life (Short Form‐12) and intuitive eating (Intuitive Eating Scale) data were collected at pre‐intervention, post‐intervention and 2 years. Outcomes were reported in BMI classes. Results: At pre‐intervention (n = 493), 11% had pre‐obesity, 25% obesity class I, 30% obesity class II and 34% obesity class III. Characteristics of participants with available data at post‐intervention (n = 290) and 2 years (n = 178) were comparable ( P > .05). Significant mean weight loss was seen at post‐intervention (−2.0 ± 0.4 kg, P < .001, n = 290) and 2 years (−4.3 ± 0.5 kg, P < .001, n = 178). All BMI classes had significant weight losses ( P < .05). Participants with higher obesity (classes II and III) had greater improvements in mental quality of life ( P < .05) and initial weight reductions ( P < .05) than those with lower classes. However, those with obesity class I had the greatest long‐term weight reductions and significant improvements in physical quality of life at 2 years ( P < .05). All BMI classes reported similar improvements in intuitive eating. No effect was found for differences in intervention format, duration or setting ( P > .05). Conclusions: The results support dietitian‐led multidisciplinary lifestyle interventions for multidisciplinary management of high‐risk patients of all BMI classes.